Expression of Mx exon-13 SNPs in Kampong-Laying Type (Kamper) chicken crossbreeds of female Lohmann brown-classic and male Pelung - Desiana Afifah; Indra Lesmana; Soenarwan Hery Poerwanto; Tri Joko; swarautama mahardhika; Budi Setiadi Daryono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Afifah D, Lesmana I, Poerwanto SH, Joko T, Mahardhika IWS, Daryono BS. 2020. Expression of Mx exon-13 SNPs in Kampong-Laying Type (Kamper) chicken crossbreeds of female Lohmann brown-classic and male Pelung. Biodiversitas 21: 1483-1487. The Gama Ayam Research Team has implemented marker-assisted selection (MAS) in selective breeding to provide a faster, more accurate, and more reliable selection of chicken. Mx gene expression has a vital role in chicken disease resistance. This research aimed to investigate the expression of Mx exon-13 single nucleotide polymorphisms (SNPs) in the population of female Layer Lohmann Brown-Classic, male Pelung, and its progenies Kampong-Laying Type (Kamper) chicken. The G1892A mutation in Mx exon-13 resulted in a change in the amino acid 631 of Mx. The substitution of serine to asparagine favored the ability of chickens to acquire immunity against viral diseases, including avian influenza. Asparagine (A allele) at position 631 is specific to Mx+ (resistant), whereas serine (G allele) is specific to Mx- (susceptible). DNA was amplified using the forward primer 5'-GCACTGTCACCTCTTAATAGA-3' and the reverse primer 5'-GTATTGGTAGGCTTTGTTGA-3' and then sequenced using the Sanger sequencing method. Four SNPs were obtained through Mx sequence alignment. They consisted of four substitutions (A20734T, C20737T, A20766G, and A20893G) with one haplotype. Mx exon-13 SNPs were detected in Pelung and Kamper. Therefore, Kamper chicken inherited the disease resistance gene of Pelung and could be a strong candidate for parental generation in the further selective breeding program.